PEMBERDAYAAN WARGA DALAM PENANAMAN TANAMAN OBAT KELUARGA - K Dewi Budiarti; Gin Gin Sugih Permana; Eva Daniati; Eti Suliyawati; Mohamad Ridwan Rifai; Angga Dipa Nagara; Rizqina Permatasari Ardiwijaya (Jurnal Pengabdian Masyarakat DEDIKASI, 2023)
Family medicinal plants are selected medicinal plants that can be planted in the yard or home environment. The selected medicinal plants are usually plants that can be used for first aid or mild medicines such as fever and cough. The presence of medicinal plants in the home environment is very important, especially for families who do not have easy access to medical services such as clinics, health centers or hospitals. Medicinal plants can be planted in pots or on the land around the house. By understanding the benefits and properties and types of plants. The purpose of this community service activity is expected to increase the knowledge of the community in Pasawahan Village about family medicinal plants and can utilize family medicinal plants around the community environment properly. Methods: The technique for implementing this activity is to conduct training, counseling and practice of planting Family Medicinal Plants (TOGA). Results: After the activity of planting family medicinal plants, the Pasawahan village community, in particular, knows the types of family medicinal plants and how to plant and After the activity of planting family medicine, a family medicinal plant demonstration site was formed. Conclusion: Community knowledge about family medicinal plants is very useful as a promotive and preventive effort so that it is necessary to increase activities that increase community knowledge such as counseling, seminars and implementation of TOGA planting activities.